Spontaneous fission in astrophysics (2024)
Spontaneous fission (SF) represents a rare yet fundamentally important nuclear decay process, with critical applications in understanding nucleosynthesis and energy generation in astrophysical environments such as neutron star mergers. This thesis focuses on the development and refinement of empirical models to predict SF half-lives, leveraging nuclear fission barriers and parity corrections to improve their predictive accuracy. The work is motivated by the need to address limitations in existing models, which often fail to accurately describe the behavior of nuclei under extreme conditions or overlook contributions from isotopes that do not naturally undergo SF. A novel approach is presented, introducing regression-based formulas that integrate macroscopic terms, such as Z2/A, alongside microscopic corrections including fission barriers (Bf ) and parity effects. These formulas have been validated against experimental half-life data from the National Nuclear Data Center (NNDC) and compared to models proposed by Möller, Mamdouh, and Zagrebaev. The results reveal that while existing models perform well within specific nuclear regions, the proposed empirical formulas provide superior agreement across a broader range of nuclei, particularly for long-lived isotopes where shell and deformation effects dominate. Furthermore, the implications of SF for astrophysical nucleosynthesis are explored, with a focus on its role as a neutron source and a termination mechanism in the rapid neutron capture process (r-process). The analysis underscores the necessity of understanding SF in environments with extreme temperatures, neutron fluxes, and magnetic fields, which significantly alter nuclear stability and reaction rates. While this study lays the groundwork for future theoretical and experimental advancements, it also highlights the importance of improving fission barrier calculations and incorporating them into more comprehensive astrophysical models. These contributions are essential for advancing our knowledge of heavy element formation and energy dynamics in explosive cosmic events.